Buttocks Beautification 3D with Calcium Hydroxylapatite (Radiesse™): An Individualized Approach to Diagnosing and Treating Contour, Sagging, and Cellulite of the Buttocks in Seven Cases - Teodoro, Matheus dos Santos; Di Sessa, David; Barros, João Henrique da Fonseca Armada; de Vasconcelos, Rossana Cantanhede Farias; Miot, Hélio Amante [UNESP] (Taylor & Francis, 2023)
Background: The demand for body procedures is increasing, and buttocks beautification is one of the most sought-after procedures in dermatological and plastic surgery clinics. Several aspects affect the beauty of this area, including sagging, cellulite, contour irregularity, and volume reduction. This makes treatment of the area more challenging. Calcium hydroxylapatite (CaHA), which may be injected into the buttocks, stimulates local neocollagenesis, provides volume replacement, increases the strength and elasticity of the dermis, and thickens the underlying superficial fascia. However, no protocol for buttocks beautification tailors the dilution and deep application of CaHA filler simultaneously according to clinical assessments and personal priorities regarding contour, sagging, and cellulite. Purpose: To report the results of a minimally invasive protocol using different dilutions of CaHA (Buttocks Beautification 3D) in the buttocks with application in different planes. The treatment was performed according to a previous individualized evaluation to improve the area aesthetically. Patients and methods: Six women and one man were submitted to the protocol. An assessment was performed to determine the shape, sagging, cellulite (in women), and patients’ preferences for buttocks beautification. The dilution, volume, depth, and injection technique for CaHA were based on these assessments. The results of the treatment were then assessed using standardized photographs and patient satisfaction. Results: We reported favorable results in six women and one man with different grades of sagging, female cellulite, and shapes of the gluteal region who were treated with CaHA injections according to a tailored protocol. All participants reported high satisfaction with the procedure. Conclusion: Highly satisfactory results were achieved in seven adult patients who were assessed and treated for the buttocks with CaHA using an individualized protocol. Prospective studies should be performed to corroborate our findings and optimize the use of Buttocks Beautification 3D as a reliable modality of treatment for this body area.
Keywords: biostimulatory treatment; calcium hydroxylapatite; neocollagenesis; Rejuvenation